ANALYSIS OF THE IMPLEMENTATION OF A PARTICIPATORY APPROACH IN THE SCHOOL LITERACY PROGRAM AT SMP NEGERI 1 CITEUREUP - Elsa Elviana; Fazida Hilya Alifa; Maftuhah; Zahruddin (SOSIOEDUKASI, 2026)
Literacy is a fundamental competence that plays an important role in improving the quality of learning and students' thinking skills. Low literacy achievement has encouraged the need to strengthen the School Literacy Movement through a more inclusive and collaborative approach. This study aims to analyze the implementation of a participatory approach in the School Literacy Program at SMP Negeri 1 Citeureup by examining the implementation process as well as its supporting and inhibiting factors. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that the participatory approach was implemented through the active involvement of the principal, teachers, students, and the school committee in the planning, implementation, and evaluation stages of the literacy program. Literacy Wednesday activities, Book Talks, classroom reading corners, as well as poetry performances, speeches, dramas, and student work presentations contributed to building a collaborative literacy culture. The main supporting factors include the commitment of school leadership, cooperation among teachers, and student enthusiasm, while the obstacles faced include limited reading resources, implementation time, and variations in student motivation. The participatory approach not only strengthens the school's literacy culture but also supports the development of students' communication skills, creativity, and self-confidence.